Catheter-Related Bloodstream Infection (CRBSI) akibat Methicillin-Resistant Staphylococcus aureus (MRSA) pada Pasien Hemodialisis: Laporan Kasus - Yogi Haditya (PT Dexa Medica, 2026)
Among dialysis patients, infection is the second leading cause of death. The use of central venous catheters (CVC) for hemodialysis (HD) is associated with increased infection rates compared with other types of vascular access. The use of CVC is associated with a 2–3 fold higher risk of infection compared with arteriovenous fistula (AVF). CVC is associated with a spectrum of infections that includes catheter-related bloodstream infections (CRBSI) at the exit site, tunnel, and catheter. CRBSI is the most clinically significant infection due to its potential for progression to sepsis and death, and represents a major complication. We reported a 40-year-old man, with CRBSI caused by methicillin-resistant Staphylococcus aureus. The patient presented with a history of fever during HD sessions that resolved upon completion of HD. The vascular access used was a temporary CVC that had been in place for 2 months prior. On physical examination, the skin surrounding the catheter double lumen (CDL) was hyperemic with remaining blood clots. Cultures obtained from the exit-site swab, blood from the tip of CVC, and peripheral blood all identified with the same result: methicillin-resistant Staphylococcus aureus. Intravenous vancomycin 1,000 mg twice daily (BID) was administered for 14 days, and source control including catheter replacement was carried out. Repeat blood culture obtained after 14 days of antibiotic therapy was negative for bacteremia,and the patient showed clinical improvement.